REGULASI INVESTASI PASAR MODAL SYARIAH DI INDONESIA - Sholeh, Habib Iman Nurdin (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2020)
This article explains about Islamic investment and capital markets in a juridical-normative perspective. Investment and capital markets are part of muamalah activities, so all activities must have a legal basis to be used as guidelines in its implementation. Investment and capital market activities, with all types, types and contracts in it are one derivative of the framework of muamalah activities in the field of Islamic economics. Juridical-normative perspectives on investment activities and Islamic capital markets, rarely found in academic literature, therefore it is important to examine the extent to which Islamic principles are adopted into positive law to serve as a legal umbrella in investment business activities. In this article, the method used by the author is a normative juridical method, which uses a problem approach with the intent and purpose of studying and reviewing applicable laws and competent regulations to be used as a basis for discussion of existing problems. Sharia norms and principles regarding investment and capital markets that can be guided have been codified in various Fatwa Dewan Syariah Nasional (DSN-MUI). Until now, DSN-MUI has issued at least 19 (nineteen) fatwas relating to investment activities and Islamic capital markets. However, in the life of the state also needs a legal umbrella so that investment activities and capital markets have the power of law, legal certainty, and justice. The legislation and regulations that have been legalized by relevant state institutions that have legal standing are 2 (two) pieces of Law and 9 (nine) Otoritas Jasa Keuangan (OJK) Regulations. Â  Keywords: Investasi, Pasar Modal, Regulasi.